1996
DOI: 10.1046/j.1365-2168.1996.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of third-degree perineal tears in labour and outcome after primary repair

Abstract: The incidence and outcome of third-degree tears following 16,583 vaginal deliveries were prospectively assessed over a 5.5-year period. Ninety-three deliveries (0.56 per cent) were complicated by a third-degree tear and the patients underwent primary repair. Eighty-one patients were reviewed 3 months postpartum at a colorectal clinic. Third-degree tears were significantly more common in primigravidae and mothers with higher birth-weight babies. They were significantly associated with the use of forceps and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
70
4
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 15 publications
15
70
4
4
Order By: Relevance
“…In agreement with other research teams we found a high frequency of endosonographic sphincter defects after primarily sutured sphincter tears 4,8,20,25 . By using an endosonographic defect scoring system we quantified the sphincter damage and described its change over time.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with other research teams we found a high frequency of endosonographic sphincter defects after primarily sutured sphincter tears 4,8,20,25 . By using an endosonographic defect scoring system we quantified the sphincter damage and described its change over time.…”
Section: Discussionsupporting
confidence: 93%
“…According to published studies, most women with anal incontinence after an obstetric sphincter tear are incontinent for gas only (gas incontinence/stool incontinence ratio of 5 : 1) 8,12,21,28 . In a 30-year retrospective study of women in three groups (obstetric anal sphincter tear, episiotomy, Cesarean delivery) 16 a surprisingly large number of middle-aged women had anal incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…The gestational age and the maternal age at delivery were not shown to be significant risk factors (p= NS). Similar studies conducted by Sultan et al [13], Walsh et al [15] and Fenner et al [16] have also demonstrated forceps delivery, primiparity, foetal birth weight over 4 kg and delay in the second stage of labour to be risk factors. In addition, Sultan et al [13], in their study, demonstrated that persistent occipitoposterior position to be a significant risk factor.…”
Section: Discussionmentioning
confidence: 56%
“…The avoidance of severe perineal trauma is of clinical importance because of the long-term morbidity for the new mothers, including perineal pain, dyspa- 175 reunia and anal incontinence, of which foecal incontinence is a particularly devastating complication [20]. As vacuum delivery is still a well-known risk factor for anal sphincter tears, it is of outstanding interest to manage the perineum during this procedure in the best way.…”
Section: Discussionmentioning
confidence: 99%